Diagnóstico de las alteraciones verticales dentofaciales - Zandra Milena Ocampo-A (Universidad de Antioquia, 2005)
Vertical dysplasias are complex entities of multifactorial origin, where the genetic and environmental factors are involved. This can affect the dentoalveolar structures, the skeletal structures or both. Accurate idenfication of these characteristics are fundamental to achieve a definitive diagnosis that will allow the establishment of an appropriate treatment plan. The purpose of this article is to integrate the general knowledge of vertical plan alterations focused on the diagnosis, evaluating the different etiological factors and facial, cephalometric, occlusal and articular characteristics of skeletal vertical dysplasias (the short face syndrome and the long face syndrome) and the dentoalveolar vertical alterations.